Immunological studies of human placentae: subclass and fragment specificity of binding of aggregated IgG by placental endothelial cells. - Johnson, P M (1976)
Fluorescein-conjugated heat-aggregated human IgG binds to endothelial cells of foetal stem vessels in cryostat sections of normal, full-term human placentae. No binding was observed using native human IgG of heat-aggregated human albumin, IgM or IgA2. No inhibition of binding of heat-aggregated human IgG was observed by pre-treatment of placental tissue sections with native IgG or non-aggregated Fc fragments. The binding was blocked using heat-aggregated Fc fragments prepared from IgG1, IgG2, IgG3 and IgG4 myeloma proteins, but not with heat-aggregated human light chains, Fab and F(ab)2 fragments of human IgG, or with heat-aggregated human IgM and IgA2. It is suggested that the placental endothelial cell receptor for aggregated IgG may function to keep immune complexes from entering the foetal circulation.